The Effect of Financial Distress, Firm Size, Leverage and Litigation Risk on The Application of Accounting Conservatism In Manufacturing Companies Listed In Indonesia Stock Exchange - Septriana, Ira; Triyono, Hermawan; Prajanto, Agung (Universitas Dian Nuswantoro Semarang, 2021)
This research aims to analyze the effect of financial distress, firm size, leverage, and litigation risk on implementing the accounting conservatism of manufacturing companies in Indonesia. The population in this research is manufacturing companies listed on the Indonesia Stock Exchanged (IDX) over 2014-2018. Research sample selection used the purposive sampling method. Obtained company data that meet the research criteria as many as 169 companies, so that the total research data is 149 data. The analysis methods in this research are multiple regression analysis. Based on the test results of the research conclude that variables of the board of financial distress, firm size, and litigation risk have no effect on accounting conservatism implemented of manufacturing companies. Meanwhile, the variable of leverage affects the accounting conservatism's implemented by manufacturing companies. Keywords: Conservatism Accounting. Financial Distress, Firm Size, Leverage, Litigation Risk